Comparison of In-hospital Outcomes of Percutaneous Coronary Intervention between Young Male and Female Patients with Acute Coronary Syndrome - Cader, Fathima Aaysha; Rahman, Afzalur; Nasrin, Sahela; Haq, M Maksumul; Amin, Md Rasul; Rahman, Mohammad Arifur; Alam, Md Sarawar; Singha, Chayan Kumar; Biswas, Eshita; Azam, MG (University Heart Journal, 2018)
Background: Acute coronary syndrome (ACS) among young people is increasingly prevalent. However, there is a scarcity of data on the gender differences of in-hospital adverse outcomes among ACS patients after percutaneous coronary intervention (PCI) among young Bangladeshis. This study was conducted to compare the in-hospital outcomes of PCI between young males and females presenting with ACS. Methods: This prospective observational study was done in the Department of Cardiology, National Institute of Cardiovascular Diseases (NICVD) fromApril 2016 to March 2017. 190 young patients with ACS and undergoing PCI were enrolled. They were equally divided into two groups, group I (young females <55 years) and group II (young males <45 years). Results: The mean age of young females and males was 43.8±6.9 years and 40.1±4.3 years respectively. Young women had significantly higher risk factors of hypertension (62.1% vs 33.7%, p<0.0010) and diabetes (57.9% vs 31.6%, p<0.001) in comparison to young men. Young women had angiographically less severe coronary artery disease (CAD), with significantly higher numbers of ACC/AHA lesion type B2 (40% vs 25.3%, p=0.03) and C (20% vs 9.47%, p=0.03), and greater frequency of multivessel disease. Overall, young women experienced greater incidence of in-hospital adverse events in comparison to young men (13.7% vs. 6.3%, p=0.09) and had significantly higher rates of severe bleeding (6.3% vs 1.1%, p=0.04) and vascular access site complications (8.4% vs 2.1%, p=0.04). Major adverse cardiac events were higher among young females, in comparison to young males (2.1% vs 0%, p=0.47). Young females experienced significantly higher rates of short-term net adverse clinical events (NACE) than young males (10.5% vs 3.2%, p=0.04). Female gender (odds ratio [OR] 11.7), diabetes (OR 2.5), hypertension (OR 1.78), decreased ejection fraction (OR 1.41) and smaller stent diameter (OR 1.15) were identified as independent predictors of adverse in-hospital outcomes among young ACS patients undergoing PCI. Conclusion: Young women with ACS presented with significantly more risk factors and experienced more adverse in-hospital outcomes after PCI, despite angiographically less severe CAD. They had significantly greater NACE, largely driven by increased rates of major bleeding. Female gender was an independent predictor of adverse in-hospital outcomes among young ACS patients undergoing PCI. University Heart Journal Vol. 12, No. 2, July 2016; 61-67